ESSENCE, OBJECTIVES, ADVANTAGES AND PROSPECTS FOR THE DEVELOPMENT OF INTERNET MARKETING - Samar Alikulov (American Journals, 2022)
Information technologies cover all spheres of our life. Marketing is no exception. The rapid development of devices and free access to the Internet from anywhere in the world are the main factors influencing the formation of marketing trends of the future and are an urgent topic at the present stage. Marketing of the future is based on the fact that the means of innovative technologies occupy a central place in the interaction between seller and buyer.
Keywords: marketing, marketing, information technology, marketing tools, Internet.